About designing : analysing design meetings - Lloyd, Peter; McDonnell, Janet (CRC Press, 2009)
Features twenty-one contributions that draw on a variety of methodological positions, research backgrounds and design disciplines, including architecture, product design, engineering, applied linguistics, communication studies, cognitive psychology, and discourse studies. This book contains an overview of design thinking research